Die verkaufte Braut komische Oper in drei Akten = Bartered bride - Smetana, Bedřich 1824-1884 (Universal Music, Deutsche Grammophon, 2007)
Otto Schenk's 1982 production of Smetana's opera about the bartered bride who finally married the young Bohemian she loved includes "...lilting melodies, lovable characters and rousing Czech folk dances."--Container
Interpr.: Lucia Popp (Marie) ; Siegfried Jerusalem (Hans) ; Karl Ridderbusch (Kezal) ; Heinz Zednik (Wenzel) ; Alfred Šramek (Kruschina) ; Gertrude Jahn (Katinka) ; Walter Fink (Micha) ; Czeslawa Slania (Agnes) ; Chor der Wiener Staatsoper ; Ballett der Wiener Staatsoper ; Orchester der Wiener Staatsoper ; Adam Fischer, conductor; Production and video direction, Otto Schenk. - Dt. gesungen. - Untertitel: dt., engl., franz., span., chin. - Aufn.: Wiener Staatsoper, 25. April 1982, live
Keywords: Operas; DVD-Video